Lattice strain and atomic replacement of CoO₆ octahedra in layered sodium cobalt oxide for boosted water oxidation electrocatalysis - Sun, Lan (2022)
Layered alkali metal oxides have been emerged as an alternative group with low-cost and promising electrocatalysts in water oxidation. The distinct layered configuration may offer some interesting possibilities to tune the intrinsic activity by regulating the intralayer edge-shared CoO6 octahedra and the CoO2 interlayer spacing/strain. In this work, electrochemical desodiation tuning method is explored on intralayer Ag, Cu, Ce-doped Na0.7CoO2 for highly active OER catalysts. It is demonstrated that the ΔGOH* value in the volcano plot is optimized by proper desodiation. Meanwhile, the lattice strain introduced along with the desodiated process modulates the ΔGOH*, according to first principle calculations. It shows that ~0.157% compressive strain in the CoO2 layers and ~1% tensile strain between CoO2 layers are introduced in the desodiated Ag doped Na0.7CoO2. Among these catalysts, the desodiated Ag-Na0.7CoO2 sample exhibits an optimal RuO2-beyond water oxidation (OER) activity with the lowest overpotential of 236 mV@10 mA/cm2, the smallest Tafel slope of 48 mV/dec and the highest mass current density of 227.8 A/g. This work provides an interesting avenues to optimize existing layered materials with inter/intralayer modifications for highly efficient water oxidation electrolysis.